2022
DOI: 10.1097/moo.0000000000000790
|View full text |Cite
|
Sign up to set email alerts
|

Management of lateral neck nodes in common and aggressive variants of thyroid cancer

Abstract: Purpose of reviewAlthough nodal metastasis in thyroid cancer does not have a major impact on outcome, it does have some prognostic implication in adverse metastasis and aggressive histology. The purpose of this review is to discuss evaluation and management of lateral neck nodes in thyroid cancer. Recent findingsThere is a high incidence of central and lateral neck node metastasis in thyroid cancer. Appropriate preoperative evaluation is key prior to first surgical procedure. The distribution of nodal metastas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…ATA recommends RAI adjuvant therapy should be considered after total thyroidectomy in intermediate-risk level WDTC [5] and RAI is frequently used as adjuvant treatment for these patients with improved survival outcomes [60]. However, within the group with intermediate-risk level, AVPTC appear to have higher rates of resistance to RAI [61]. Despite this fact, RAI is still commonly used in AVPTC, recognizing that AVPTC may be less avid.…”
Section: New Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…ATA recommends RAI adjuvant therapy should be considered after total thyroidectomy in intermediate-risk level WDTC [5] and RAI is frequently used as adjuvant treatment for these patients with improved survival outcomes [60]. However, within the group with intermediate-risk level, AVPTC appear to have higher rates of resistance to RAI [61]. Despite this fact, RAI is still commonly used in AVPTC, recognizing that AVPTC may be less avid.…”
Section: New Perspectivesmentioning
confidence: 99%
“…PORT may be required in selected patients with a high risk of recurrence, which may be either surgically incurable or life-threatening [61]. Kazaure et al [8] demonstrated that PORT led to improved locoregional recurrence-free probability; however, this did not translate into improved disease-specific survival or overall survival.…”
Section: New Perspectivesmentioning
confidence: 99%